(untitled) (Eurasian Journal of Ecology, 2020)
The problem of pollution of natural ecosystems with oil and oil products is extremely acute in many countries of the world, including Kazakhstan. A significant part of oil-contaminated sites is located in regions with a hot climate, and in such countries studies are underway to isolate thermotolerant oildegrading microorganisms with a view to their further use for remediation of oil-contaminated territories. The circle of such microorganisms is quite wide and diverse. The effectiveness of the method of bioremediation of oil-polluted ecosystems largely depends on biotic and abiotic factors, for example, salinity, temperature, ability to produce surfactants, pH, etc. Earlier from the soils of Western Kazakhstan, we isolated and identified thermotolerant oil-oxidizing microorganisms capable of oxidizing oil hydrocarbons in a wide temperature range. The aim of this work was to study the ability of active thermotolerant oil-oxidizing microorganisms to degrade oil at different concentrations of mineral salts (Cl-, SO42-) and to determine the emulsifying activity to assess their biotechnological potential. It was established that all selected strains are halotolerant. Moreover, the temperature factor influenced the degree of oil degradation in the presence of mineral salts. The highest percentage of oil degradation was at 35°C. At this temperature, strains K-3, 4/5, P1-35-14 showed high activity at all studied NaCl concentrations (3, 5 and 10%) – 73.6-85.9%, 62.7-91.1 % and 73.6-75.7%, respectively. At 40°C, the strain IP-40-4 showed the highest activity – 41.4-51.2%. At 50°C, the destruction ability of the studied cultures was approximately at the same level at all NaCl concentrations. The cultivation of selected strains with a high content of MgSO4 in the medium showed that the K-3 strain was the most stable, which remained highly active at all temperatures. It was shown that active strains of thermotolerant oil-oxidizing microorganisms had emulsifying activity. High values of emulsifying activity are observed at a temperature of 35°C, and with a subsequent increase in temperature, the formation of surfactants decreased. At 35°C, strain P2-35-9 had the greatest emulsifying activity, and at 40°C and 50°C – strain K-3. Key words: bioremediation, thermotolerant hydrocarbon-oxidizing bacteria, salinity, halotolerance, emulsifying activity.